SETTING UP TRIAGE SERVICES IN THE EMERGENCY DEPARTMENT: EXPERIENCE FROM A TERTIARY CARE INSTITUTE OF PAKISTAN. A JOURNEY TOWARD EXCELLENCE - Khursheed, Munawar; Fayyaz, Jabeen; Jamil, Ahsan (Journal of Ayub Medical College Abbottabad, 2015)
The history of triage started from the French battle field for prioritizing patients. Emergency triage was started in early 1950's inUSAin order to treat the sickest first. It has now become an integral component of all emergency departments (ED). The basic aim of triage is not only to sort out patients according to the criticality of their illness, but it also serves to streamline the patient flow. This will ultimately enable the ED physician to provide right management at the right time to the right patient in the available resources. In turn has a positive impact in reducing the ED overcrowding. The history of triage at AKUH-ED dated back in2000. Inthe beginning physicians and nurse both were assigned to triage desk where they use to sort out the patient according to presenting complaints. At that time the documentation was manual with locally developed triage priorities. With the expansion of ED in 2008, responsibility of triage was shifted to nursing services. Triage policy was established and implemented. Specific triage protocols were developed for guidance and uniformity of care. Manual recording system was replaced by computerized triage data entry software. Enabling the department to monitor patient quality care indicators like total number of patients triaged, triage category, lag time reports and left without being seen by physicians.